Cognitive Development in Active eLearning - Ratniece, Dace (International Journal of Engineering and Technology, 2018)
There has been an ongoing debate amongst educators about the role of memory versus intelligence in fostering effective learning. It has long been held that learners are more successful in retaining new content if they consciously think about whatâ€™s being taught, as opposed to simply memorizing what they see on the slides or on a computer screen. The learning theory of cognitive development plays a huge role in the case of the former approachâ€”understanding by thinking. Because of its very nature, where time and distance often separate instructors and learners, the cognitive process plays an even more important role in eLearning.Nowadays learning style has been changed. A suitable technique for teaching courses needs to be adopted to improve the learning effectiveness of students. Modern technology and an up-to-date tool affect student learning abilities, especially in 21st century learning, which requires students to learn by doing. Active learning and eLearning tools and environment are aspects that can encourage students to have high learning efficiency.Â Â